Analysis of Interface Design in the Game Honkai Star Rail Using the Usability Heuristics Principles of UI - Saputra, M Garry; Andelina, Ika Resmika (Gameology and Multimedia Expert, 2025)
There are several factors that can make a game worth playing to achieve an achievement and popularity. One of these factors is the User Interface. The interface in the game plays a very important role in showing the quality of a game. The interface in the game is an important bridge that connects players with the game mechanics, story, and overall experience. HSR is one of the Turn-Based RPG themed games that has been quite popular since the game was first released. The HSR game interface is the focus of the analysis that will be carried out in this study. This aims to understand and prove that the User Interface plays a very important role in making games with good quality. The analysis will be carried out using the Usabilty Heuritics Principle of UI method by Jakob Nelseen where the analysis is carried out based on the points in the principle in detail so that it can produce research results that can be used as references and guidelines for interface designers in the process of creating game interfaces in the future.